0130 Incidence of work-related respiratory ill health attributed to cleaning agents: occupational and chemical determinants. (21st August 2017) - Carder, Melanie; Seed, Martin; Agius, Raymond
Abstract : Introduction: Exposure to cleaning products has been shown to be associated with adverse respiratory outcomes. The aim of this study was to investigate the medically reported incidence and occupational determinants of work-related respiratory disorders attributed to cleaning agents, and to explore the role of a chemical taxonomy and 'Quantitative Structure Activity Relationships' (QSAR) in categorising hazards and their mechanisms. Methods: Cases of work-related respiratory disease attributed to cleaning agents were identified and extracted from SWORD (Surveillance of Work-Related and Occupational Respiratory Disease), 1989–2015. Incidence, trends in incidence and incidence rate ratios (IRRs) by occupation were investigated. Agents were classified by chemical type and QSAR hazard indices were determined on selected typical organic chemicals. Results: A reported 667 cases (6% of the non-asbestos related cases) were attributed to cleaning agents. Diagnoses were predominantly asthma (58%) and inhalation accidents (29%). The agents were classified in ten specific chemical categories with the most frequently reported being aldehydes (33%) and chlorine/releasers (25%). An overall decrease in incidence of −4.4% (95% CI: −6.8, −2.0) per year was observed. A large variation in risk was observed with the incidence for the highest risk occupation, 'launderers, dry cleaners and pressers', being more than 50 times the average of all other occupations. A high QSAR asthma hazard index was found in agents which were likely sensitisers. Conclusion: The data highlight a number of occupations at increased risk of adverse respiratory outcomes attributed to cleaning agents. Chemical features of the cleaning agents helped distinguish between sensitising and irritant agents.